The Impact of Nationally Coordinated Pharmacy-Based Asthma Education Intervention - Shelley Anne Diamond; Kenneth Ross Chapman (Canadian Respiratory Journal)
OBJECTIVE: To assess the impact of a nationally coordinated pharmacy-based educational intervention on self-management behaviour and markers of asthma control in self-referred patients with asthma.